The effect of budget goal clarity, organizational commitment, accounting control, and adherence to laws on the perception of government performance of Central Lombok Regency - Fathul Jawadi; H. Prayitno Basuki; Lukman Effendy (STIE Perbanas Surabaya, 2016)
This research was conducted to examine the effect of budget goal clarity, organization-al commitment, accounting control and adherence to laws on the perceptions of gov-ernment performance. The respondents consists of the structural positions in a region-al government such as the chair person of a body, an agency, a division, a subdivision, and the team of government performance report of Central Lombok Regency. It used a purposive sampling method to get the respondents. They were asked to respond a set of questions in a questionnaire. Of the 90 questionnaires distributed, only 78 question-naires were valid for analysis. The data were analyzed using multi-linear regression method with SPSS 18.0. The results show that budget goal clarity and organizational commitment have an effect on the perception of government performance. The ac-counting control and adherence to laws have no effect on the perceptions of govern-ment performance. It implies that is important to have observation of planning and budget execution as well as the local government commitment to make the financial transaction control and adherence of laws run effectively. The local government shall obey the existing laws in order to integrate the strategic plan system, governance accounting system, budgeting system and exchequer system into an integrated system by improving human resource and information technology.